2020
DOI: 10.1364/osac.395767
|View full text |Cite
|
Sign up to set email alerts
|

Inverse designed achromatic flat lens operating in the ultraviolet

Abstract: We demonstrate an inverse designed achromatic, flat, polarization-insensitive diffractive optic element, i.e., multilevel diffractive lens (MDL), operating across a broadband range of UV light (250 nm -400 nm) via numerical simulations. The simulated average onaxis focusing efficiency of the MDL is optimized to be as high as ~86%. We also investigate the off-axis focusing characteristics at different incident angles of the incoming UV radiation such that the MDL has a full field of view of 30˚. The simulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…3(c  is the wavelength of the center frequency ( 12GHz), which is 24.98 mm. The average value of the broadband F  is equal to 13.49 mm which means that the average shift in focal lengths equals to 2.38% [25]. All the presented results verify that the implemented MO-DE algorithm satisfactorily suppresses the focal shift over a broadband range.…”
Section: Design Methodology and Numerical Results Of Amdlsupporting
confidence: 59%
See 2 more Smart Citations
“…3(c  is the wavelength of the center frequency ( 12GHz), which is 24.98 mm. The average value of the broadband F  is equal to 13.49 mm which means that the average shift in focal lengths equals to 2.38% [25]. All the presented results verify that the implemented MO-DE algorithm satisfactorily suppresses the focal shift over a broadband range.…”
Section: Design Methodology and Numerical Results Of Amdlsupporting
confidence: 59%
“…To verify broadband operation functionality of the designed AMDL, the maps of the experimentally measured cross-sectional intensity profiles on the optical axis and on the lateral direction of focal point are presented in Figs. 5(a  is equal to 12.85 mm which means that the average shift in focal distances equals to 7.01% [25]. As can be seen from Fig.…”
Section: Experimental Analysis Of Achromatic Focusing Effectmentioning
confidence: 74%
See 1 more Smart Citation
“…5(a), the solar radiation covers the ultra-broad bandwidths from the NIR region (from 780 nm to 2526 nm) to the deep-UV (DUV) range (from 190 nm to 280 nm) [18,176,177]. According to the aforementioned introduction of the building materials, a meta-lens that is formed using different materials generally operates at the corresponding spectrum, and thereby, we will introduce the high-focusing-efficiency optical meta-lenses in terms of their working wavelengths, including the NIR [169,174,[178][179][180][181][182], visible [134,152,164,165,[183][184][185][186][187], and UV bands [146,148,149,[188][189][190][191][192][193]. The focusing efficiency is defined as the optical power confined within a focal spot divided by the corresponding incident power.…”
Section: Focusing Efficiencymentioning
confidence: 99%
“…We recently showed that MDLs have equal or better performance when compared to metalenses, which are harder to design and manufacture [11]. MDLs have already been demonstrated in the ultraviolet [12], visible [13], near infrared [14,15], short wave infrared, [16] long-wave infrared [17], THz [18], and microwave [19] bands. Magnification in an imaging system was also demonstrated by coupling two MDLs [20].…”
mentioning
confidence: 99%